2022
DOI: 10.1007/s43390-022-00618-1
|View full text |Cite
|
Sign up to set email alerts
|

Current models to understand the onset and progression of scoliotic deformities in adolescent idiopathic scoliosis: a systematic review

Abstract: 1 Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…While there is no universally accepted theory explaining the pathogenesis of AIS, anterior column overgrowth is a frequently studied phenomenon, [69][70][71][72][73][74][75] with ongoing debate surrounding the cause-effect relationship with wedging and rotation. 76,77 Our included studies also reported sagittal wedging in lower junctional vertebrae and discs, which was associated with increases in Cobb angle. 49,51 Among thoracic, thoracolumbar, and lumbar curves, thoracic hypokyphosis was consistently observed in 3D studies.…”
Section: Sagittal Deformitymentioning
confidence: 88%
“…While there is no universally accepted theory explaining the pathogenesis of AIS, anterior column overgrowth is a frequently studied phenomenon, [69][70][71][72][73][74][75] with ongoing debate surrounding the cause-effect relationship with wedging and rotation. 76,77 Our included studies also reported sagittal wedging in lower junctional vertebrae and discs, which was associated with increases in Cobb angle. 49,51 Among thoracic, thoracolumbar, and lumbar curves, thoracic hypokyphosis was consistently observed in 3D studies.…”
Section: Sagittal Deformitymentioning
confidence: 88%